Introduction: Labor Travels, Art Forms. Issue 5 (May 2016) - Doyle, Laura
Abstract: This GCP special cluster "Labor Travels, Art Forms" highlights the ways that laborers and arts have traveled together through transnational political economies. The editor outlines the models and genealogies presented in the essays and proposes that there is more to consider about what might be called "labor's aesthetic diasporas." Exploring some of these possibilities, the Introduction asks what different story of the arts emerges when we follow links between the history of aesthetics and the history of labor? What fuller history of labor comes into view? Might we enrich current analyses of globalization through interdisciplinary study of arts' labored travels as they have shaped states and economies? Finally, how might we differently conceive of the mediating work of the arts in this light?